Negotiating research in the shadow of migration control: access, knowledge and cognitive authority. (30th July 2019) - Rosset, Damian; Achermann, Christin
Abstract : This article recounts the failure to gain access to the Swiss asylum agency's 'country of origin information' (COI) unit and how it negatively impacted access to similar research sites in Europe. As producers of indispensable expert knowledge, these units play an important instrumental and symbolic role in asylum procedures and policies. Interpreted as a situated case of knowledge control, rather than a general resistance to research within the institution, the denial of access reveals how the intended research challenged gatekeepers' idealised construction of COI – both as a type of knowledge and as a field of practice. The negotiation about access gradually shifted to other topics, such as the researcher's competence, the field's situation and the nature of legitimate knowledge – all related to politics of expertise and the COI units' legitimising functions in the wider migration apparatus. The negotiation became a competition over cognitive authority and the monopoly of legitimate knowledge production about the field. By black‐boxing country information, the gatekeepers fostered the illegibility of bureaucratic processes and the legibility of the state as discourse. Analysing the 30‐month negotiation process also reveals the difficulties to seize the contours of the state when encountering transnational bureaucratic fields. Négocier la recherche dans l'ombre du contrôle migratoire : accès, savoir et autorité cognitive: Cet article décrit l'insuccès à accéder à l'unité d'information sur le pays d'origine (COI) de l'administration suisse responsable de l'asile et son impact négatif sur l'accès à des sites de recherche similaires en Europe. En tant que productrices d'un savoir expert essentiel, ces unités jouent un rôle instrumental et symbolique important dans les procédures et les politiques d'asile. Interprété comme un cas situé de contrôle du savoir, plutôt que découlant d'une résistance générale à la recherche au sein de l'institution, le refus d'octroyer l'accès révèle la façon dont la recherche envisagée remettait en question la construction idéalisée des COI par les « gatekeepers » – à la fois comme type de savoir et comme champ de pratique. La négociation sur l'accès a peu à peu dérivé vers d'autres sujets, tels que la compétence du chercheur, le positionnement du terrain et la nature du savoir légitime – tous liés à la politique de l'expertise et aux fonctions de légitimation des unités COI dans le dispositif migratoire plus large. La négociation s'est transformée en compétition sur l'autorité cognitive et le monopole de la production légitime de savoir sur le terrain. Par la mise en boîte noire des informations sur les pays, les « gatekeepers » ont protégé l'illisibilité des processus bureaucratiques et la lisibilité de l'État en tant que discours. L'analyse du processus de négociation de 30 mois révèle également les difficultés à saisir les contours de l'État lorsque l'on rencontre des champs bureaucratiques transnationaux.